Building a foundation for local community participation in tourism planning in Hwange District, Zimbabwe - Mpofu, Praywell William; Van Der Merwe, Petrus (Frontiers in Sustainable Tourism, 2025)
IntroductionThis study explored the critical factors for building a foundation for local community participation in tourism planning in the Hwange District, Zimbabwe. The participation of local communities in tourism planning is critical for good governance, fostering a symbiosis between tourism development and community aspirations, sustainable development and effective conservation in nature-based destinations of developing countries.MethodsA qualitative approach grounded in the interpretivist paradigm, involving semi-structured interviews with 22 key informants, was adopted, and the data were thematically analyzed.Results and discussionThe key findings indicate that fully implementing all key participatory legislation and policies, revitalizing participatory sectoral planning legislation, acknowledging and remedying conservation and tourism development injustices and costs, addressing communal land tenure and security and revitalizing and reforming community-based conservation are critical for building a foundation for effective local community participation in tourism planning. The study recommends the creation of an overarching, district-level integrated planning framework centered on the district's local authorities to lead tourism planning for coordinated and inclusive development. The insights from this study contribute to the burgeoning literature on building the role of local communities in tourism planning in nature-based destinations of developing countries and lay a foundation for dialogue and further related research. The findings could also inform tourism and conservation legislation and policies aimed at advancing local community empowerment and sustainable development in developing countries.